2012
DOI: 10.1016/b978-0-12-394280-7.00005-1
|View full text |Cite
|
Sign up to set email alerts
|

Activation-Induced Cytidine Deaminase in Antibody Diversification and Chromosome Translocation

Abstract: DNA damage, rearrangement and mutation of the human genome are the basis of carcinogenesis and thought to be avoided at all costs. An exception is the adaptive immune system where lymphocytes utilize programmed DNA damage to effect antigen receptor diversification. Both B and T lymphocytes diversify their antigen receptors through RAG1/2 mediated recombination, but B cells undergo two additional processes – somatic hypermutation (SHM) and class switch recombination (CSR), both initiated by Activation Induced D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 121 publications
(226 reference statements)
0
23
0
Order By: Relevance
“…Consequently, genomic occupancy of Spt5 is centered around transcription start sites (TSSs) (Pavri et al, 2010; Rahl et al, 2010). Structural studies of DSIF/RNAP complexes have shown Spt5 interacts with a region of RNAP very close to the transcription bubble (Klein et al, 2011a; Martinez-Rucobo et al, 2011), prompting the suggestion that Spt5 may tether AID onto RNAP II in close proximity to ssDNA (Gazumyan et al, 2012). Consistent with this hypothesis, genome wide ChIP studies have found AID genomic occupancy concentrated near TSSs (Yamane et al, 2011).…”
Section: Overview Of Aid Function In Immunoglobulin Diversificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, genomic occupancy of Spt5 is centered around transcription start sites (TSSs) (Pavri et al, 2010; Rahl et al, 2010). Structural studies of DSIF/RNAP complexes have shown Spt5 interacts with a region of RNAP very close to the transcription bubble (Klein et al, 2011a; Martinez-Rucobo et al, 2011), prompting the suggestion that Spt5 may tether AID onto RNAP II in close proximity to ssDNA (Gazumyan et al, 2012). Consistent with this hypothesis, genome wide ChIP studies have found AID genomic occupancy concentrated near TSSs (Yamane et al, 2011).…”
Section: Overview Of Aid Function In Immunoglobulin Diversificationmentioning
confidence: 99%
“…Consistent with this hypothesis, genome wide ChIP studies have found AID genomic occupancy concentrated near TSSs (Yamane et al, 2011). Co-localization of RNAP II, Spt5, and AID near TSSs has led several groups to propose an RNAP II stalling model of AID function whereby stalled transcription complexes provide a platform to recruit AID to ssDNA target sites (Gazumyan et al, 2012; Kenter, 2012; Storb, 2014; Sun et al, 2013b). …”
Section: Overview Of Aid Function In Immunoglobulin Diversificationmentioning
confidence: 99%
“…AID acts on C residues in the DNA of the genomic immunoglobulin loci in activated lymphocytes to trigger antibody gene diversification whereas APOBEC3 family members, of which there are seven in humans, act on C residues in the DNA of viral replication intermediates (usually in the cytoplasm) as part of a host restriction pathway. Off-target deamination by AID results in nucleotide substitutions and genomic rearrangements in B lymphocyte tumours, some of which are implicated in oncogenesis (reviewed by Gazumyan et al, 2012). Although AID is the only member of the AID/APOBEC family known to act physiologically on endogenous nuclear DNA, it is possible that other members of the AID/APOBEC family might occasionally get access to the nucleus and cause cancer-associated genomic damage or mutation (Harris et al, 2002; Beale et al, 2004; Vartanian et al, 2008; Stenglein et al, 2010; Landry et al, 2011; Nik-Zainal et al, 2012; Nowarski et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Second, modified bases within the DNA context are targeted principally by base excision repair [17] and, in some cases, by the mismatch repair machinery [18], or, rarely, by nucleotide excision repair [19] as well. Recently, it has became evident that the cellular 'infrastructure' for base excision and mismatch repair is also exploited in signal transduction leading to immunoglobulin gene diversification and active DNA demethylation [20][21][22][23][24]. Hence, the distinction between the harmful versus signalling role of modified bases becomes less clear and such definitions require an assessment of the cellular context (cell status, developmental stage, cell cycle stage, etc.)…”
Section: Non-orthodox Bases In Dna: Production and Eliminationmentioning
confidence: 99%